Media Consumption Patterns and Preferences among Young Adults: A Survey Study - nugrah juniar umar; hastuti hastuti; wandi wandi (State Islamic Institute of Bone, Indonesia, 2023)
This research examines the media consumption pattern and preferences among young adults, emphasizing the importance of udnerstanding their engagement with media. Using a survey methid, the data were taken from 50 respondents by considering specific criteria of young adults. The data were taken by using questionnaire through a close-ended questionnaire. the findings reveal that young adults engage with various media platforms, with streaming services and social media being the most popular choices. They spend a significant amount of time consuming media content, primarily in the range of 2-4 hours per day. The preferred media genres include entertainment, music, news, sports, and lifestyle, among others. Infuencers on the media also plays significant role in shaping the attitude and behavior of young adults.